In Vitro Mass Propagation of Ornamentally and Medicinally Important Coelogyne flaccida Lindl. through Pseudobulb Segments - Kaur, Saranjeet; Bhutani, K.K. (Plant Tissue Culture and Biotechnology, 2013)
Regeneration competence of pseudobulb segments of Coelogyne flaccida, procured from in vitro grown cultures, was assessed in MS and Mitra (M) medium alone and in combinations with BA (4.44 ?M), Kn (5.65 ?M), NAA (5.37 ?M), and coconut water (CW 10%). Juvenility of the tissues, chemical stimulus, and position of the explants (apical/basal) were the key factors in initiating the response. The explants from pseudobulbs (>0.8 cm in length) did not regenerate whereas those from younger ones (<0.8 cm in length) regenerated. The response frequency and time taken for the development of plantlets also varied with the growth stimulus. Maximum number of shoots was obtained from the basal segments (nodal and extra?nodal regions), cultured in MS + NAA/NAA + BA forming 10.25 ± 0.50 and 10.00 shoots, respectively. The apical segments formed shoots only from apical meristem. The shoots rooted in the same nutrient medium and formed plantlets. Plant Tissue Cult. & Biotech. 23(1): 39?47, 2013 (June) DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15558